Association of angiographic severity of coronary artery disease and erectile dysfunction based on IIEF-5 score - Hosen, M. Imam; Hossain Khan, M. Monir; Ghosh, Sujit Kumar; Belayet, Taslima Binta; Islam, M. Azharul; Rahman, Mohammad Atikur; Abdullah-Al-Numan; Arju, Sadia; Zaman, M. Hasan; Shadly, Tausif Amim (International Journal of Research in Medical Sciences, 2025)
Background: Erectile dysfunction (ED) is common in patients with coronary artery disease (CAD). Atherosclerosis is a shared mechanism for vasculogenic ED and CAD, suggesting a potential correlation. The objective was to evaluate the association of angiographic severity of coronary artery disease & erectile dysfunction based on IIEF-5 score. Methods: This cross-sectional study was conducted at NICVD, Dhaka, on 60 patients with CAD and ED. Patients were divided into Group I (Gensini <20, n=30) and Group II (Gensini ≥20, n=30). ED was assessed using the IIEF-5 questionnaire, and IPA angiography was performed in the same setting. Results: Mean IIEF-5 score was lower in severe CAD (Group II: 13.67±4.17 vs Group I: 15.93±3.14, p=0.021). Significant IPA stenosis (>50%) was more common in Group II (43.3% vs 20%, p=0.042). Spearman’s correlation showed a negative correlation between Gensini and IIEF-5 scores (ρ=-0.475, p=0.01) and a positive correlation with IPA stenosis (ρ=0.410, p=0.03). Logistic regression identified severe CAD (OR 9.13, 95% CI 1.37–60.99) and diabetes mellitus (OR 4.75, 95% CI 1.29–46.33) as predictors of IPA stenosis. Conclusion: Severity of CAD is inversely associated with erectile function and positively correlated with IPA stenosis.